2020
DOI: 10.1007/s12250-020-00203-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Treatment of 2019-nCov Pneumonia Patients in Wuhan: Report of A Couple Cases

Abstract: nCoV) has caused more than one hundred cases in Wuhan (WMHC 2020). During a retrospective study of recent pneumonia patients in our department, we found two patients who are likely being infected with the 2019-nCoV. During the hospitalization, those two patients were appropriately treated, and both were discharged within two weeks. Thus, we are reporting the clinical features and treatment regiment, and hope the information and experience can be shared.The two patients were a couple. The male was 38 years old,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 2 publications
4
44
1
1
Order By: Relevance
“…In this study, we exhibited clinical data of 117 cancer patients and paired non-cancer patients with nuclei acid-con rmed COVID-19 infections. Similar to previous studies, fever and cough were the main symptoms and digestive symptoms were infrequent, which indicates a difference in viral tropism as compared to MERS-CoV, SARS-CoV, and seasonal in uenza [7,8] Our study demonstrated that cancer patients had more prominent laboratory abnormalities than noncancer patients, accompanied with cancer patients seriously ill as compared to patients without history of cancer [1,9,10]. 28 of the 117 cases progressed to severe pneumonia as of March 30, 2020, and died during hospitalization.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we exhibited clinical data of 117 cancer patients and paired non-cancer patients with nuclei acid-con rmed COVID-19 infections. Similar to previous studies, fever and cough were the main symptoms and digestive symptoms were infrequent, which indicates a difference in viral tropism as compared to MERS-CoV, SARS-CoV, and seasonal in uenza [7,8] Our study demonstrated that cancer patients had more prominent laboratory abnormalities than noncancer patients, accompanied with cancer patients seriously ill as compared to patients without history of cancer [1,9,10]. 28 of the 117 cases progressed to severe pneumonia as of March 30, 2020, and died during hospitalization.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, we provided epidemiological and clinical data of 24 asymptomatic COVID-19 infections identified from the screening of close contacts in Nanjing, Jiangsu Province. These asymptomatic cases were mildly ill as compared to those previously reported in Wuhan, Hubei (Guan et al, 2020;Huang et al, 2020;Zhang et al, 2020). None of the 24 cases developed severe pneumonia as of Feb18, 2020, and only 5 cases showed typical symptoms during hospitalization.…”
Section: Discussionmentioning
confidence: 50%
“…5 For further investigation, the researchers of the present study evaluated all the existing reports on treatment of COVID-19 patients, which led to finding one clinical trial 4 and 12 case-report/ case-series studies. 1,3,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] There was no mention of prescribing NSAIDs in any of these studies. This might be because of no NSAID being prescribed, which is very unlikely; or it might just be that the In this study, use of ibuprofen has been suggested for controlling the patients' fever (fever over 38.5° Celsius).…”
Section: Discussionmentioning
confidence: 99%